Composition and spatial structure of five associations of forests of Pinus durangensis - Graciano-Ávila, Gabriel; Alanís-Rodríguez, Eduardo; Rubio-Camacho, Ernesto A.; Valdecantos-Dema, Alejandro; Aguirre-Calderón, Oscar A.; González-Tagle, Marco A.; Treviño-Garza, Eduardo Javier; Corral-Rivas, José Javier; Mora-Olivo, Arturo (Instituto de Ecología, A.C., 2020)
The spatial structure reflects the pattern of arrangement of trees on the ground and is a basic element to understand the dynamics of forest ecosystems. The objective of the present investigation was to evaluate the bivariate structural characteristics of five different associations of Pinus durangensis forests, identifying the similarities and differences in the bivariate distribution of uniformity of angles, dominance and mingling. The data comes from five quadrate sites with an area of 2500 m2, each established in different forests of P. durangensis in the Sierra Madre Occidental. For each site, the average height, average diameter and crown coverage were determined, as well as the species mingling index, angle uniformity and dominance indexes. The indices were combined two to two to obtain three bivariate distributions. The pure forest of P. durangensis presented individuals with higher height, while the largest diameter was found in the association with P. teocote. The mingling index (Mi) indicates that only in the pure forest there is a low species mingling. The uniformity angle index (Wi) shows that trees generally present a random distribution. The values of dominance (Ui) show that in all the sites there are all the social classes represented in an equitable way. The indexes and their combinations adequately describe the spatial distribution of the trees and their relationship with their closest neighbors. The information obtained from the combination of the structural variables contribute to improve the understanding of the spatial structure of the forest, and in addition to contributing to the regulation of cutting intensity and ensuring sustainable management.